ISM‐band 902‐ to 928‐MHz FSK transceiver with scalable performance for medical devices. (4th September 2018) - Zgaren, Mohamed; Moradi, Arash; Tanguay, Louis‐François; Sawan, Mohamad
Summary: A 902‐ to 928‐MHz industrial, scientific, and medical band transceiver using a wake‐up link for wireless body area networks wearable and implantable medical devices is presented. The design reaches exceptionally low‐power dissipation and provides an adapted data‐rate by gathering the advantages of frequency‐shift‐keying (FSK) and amplitude‐shift‐keying (ASK) modulation techniques. Transmitter (Tx) includes a new efficient FSK modulation scheme to generate up to 20 Mb/s of data‐rate and consumes around 0.084 nJ/b. The integrated receiver (Rx) is based on a new FSK‐to‐ASK conversion technique using on‐off keying fully passive wake‐up circuit (WuRx) with energy harvesting from radio frequency link. The adopted scheme leads to the scalability of energy consumption versus data‐rate at constant transceiver sensitivity, insuring high‐performances requirements. The transceiver is implemented in IBM 0.13‐ μ m CMOS process. The WuRx achieves a sensitivity of −53 dBm while the main receiver shows −78‐dBm sensitivity. Thanks to the simplified hardware, the receiver consumes only 640  μ W while the transmitter uses 1.4 mW from 1.2‐V supply voltage. Abstract : In this paper, it was found that is possible to combine both ASK and FSK modulation techniques in full low‐power RF transceiver in order to achieve scalable data‐rate design. This is possible due to the new FSK to ASK converter block.